Diet and lifestyle habits associated with caries in deciduous teeth among 3- to 5-year-old preschool children in Jiangxi province, China - Liwei Zeng; Yixuan Zeng; Yin Zhou; Jianqiong Wen; Li Wan; Xiaoyan Ou; Xiaojun Zhou (BMC, 2018)
Abstract Background The purpose of this study was to investigate the status of caries in deciduous teeth and the effect of diet and lifestyle habits on dental caries among 3- to 5-year-old preschool children in Jiangxi Province, China. Methods In total, 2880 cases involving preschool children were selected by stratified cluster sampling. The dental examination methods and criteria followed the WHO guidelines. SPSS 19.0 was used for the statistical analysis. Chi square tests were used to compare the caries prevalence among children with different social characteristics. Non-parametric tests were used to compare the decayed, missing and filled teeth (dmft) index values. Univariate and multivariate regression analyses were used to study the effect of diet and lifestyle habits on dental caries. Results The caries prevalence among the 2880 cases of 3- to 5-year-old preschool children in Jiangxi Province, China was 49.13%. There was no gender difference in this rate (P > 0.05). The caries prevalence increased with age (P < 0.05). The prevalence of caries in the rural areas was higher than that in the urban areas (P < 0.05). The deciduous central incisors and deciduous molars had a higher caries prevalence than the other deciduous teeth. According to the multivariate logistic regression analysis, the caries risk increased with living in a rural area, exclusive breastfeeding, greater frequency of daily snacking, high frequency of snacking before sleep and beginning to brush teeth at a late age; the caries risk decreased when parents helped their children brush their teeth. Conclusion The caries prevalence among 3- to 5-year-old preschool children in Jiangxi was lower than the level throughout the country and lower than the rate in other developing countries. The children's diet and lifestyle habits were closely related to dental caries. Parents and children should be more aware of oral health, and parents should help their children develop healthy lifestyle behaviours.